Implementation of paddy drying technology: Introducing small/medium paddy dryers in remote areas - Alam, Md. Monjurul; Kalita, Prasanta Kumar; Saha, Chayan Kumer; Sarkar, Surajit; Winter-Nelson, Alex (International Food Policy Research Institute, 2024)
Grain drying has become increasingly challenging for the Bangladesh food system as postharvest innovations have not kept pace with production growth and an increasing volume of grain is harvested during wet or foggy periods, when conventional open-air drying is problematic. This activity sought to build capacity for mechanical dryer service provision by small-scale entrepreneurs and to demonstrate a model for providing mobile grain drying services through entrepreneurs using a locally manufactured small-scale dryer. In coordination with Ministry of Food officials, the project selected 20 farmers to train as mechanized drying service providers, provided them with use of small-scale mobile batch dryers, and deployed them in rural areas from which Local Supply Depots (LSDs) source grain. The service providers were active in Bogura and Rangpur Districts in late May 2023, during the closing phases of the Boro harvest season. The pilot revealed nuances of the costs of operation and indicated potential for viable business activities, especially in areas where open-air drying is relatively costly or inadequately available. Additionally, a scoping visit to Naogaon District revealed significant interest in mechanized drying services. The findings suggest a value to additional observation of the service providers to document capacity utilization over an Aman season and a full Boro season. Such observations would allow confirmation about parameters related to annual capacity utilization which are important determinants of business viability